2017
DOI: 10.1111/ijn.12509
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, health behavioral, and self‐management abilities associated with disease severity among patients with chronic obstructive pulmonary disease: An exploratory study

Abstract: This study aimed to identify the association between demographic characteristics, health behaviors, self-management abilities, and disease severity among patients with chronic obstructive pulmonary disease (COPD). The study was conducted from January to December 2015 in 4 hospitals in China. The DOSE index was assessed by grade of dyspnea (D), airflow obstruction (O), current smoking status (S), and frequency of exacerbation in the last year (E). Self-management abilities were assessed by the COPD self-managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The DOSE index comprises Dyspnoea, airflow Obstruction, Smoking status and COPD Exacerbation components (Table 1), 10 and has been shown to be associated with respiratory failure and healthcare utilisation, 10 future exacerbation, 11 mortality, 12,13 physical activity and BMI, 14 and worsening health status as measured by self-reported Clinical COPD Questionnaire. 15 Several practical advantages further commend its use in primary care in preference to other available indices.…”
Section: Introductionmentioning
confidence: 99%
“…The DOSE index comprises Dyspnoea, airflow Obstruction, Smoking status and COPD Exacerbation components (Table 1), 10 and has been shown to be associated with respiratory failure and healthcare utilisation, 10 future exacerbation, 11 mortality, 12,13 physical activity and BMI, 14 and worsening health status as measured by self-reported Clinical COPD Questionnaire. 15 Several practical advantages further commend its use in primary care in preference to other available indices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it became clear that SM skills should not be evaluated as a single component but should be evaluated together with various components that may have an effect, especially SpM. In various studies, it has been reported that the COPD stage is effective in SpM as in our study (Chen et al, 2016;Wang et al, 2017), whereas some studies have revealed a negative correlation (Chen et al, 2008;Vogelmeier et al, 2020). These results in the literature are associated with the fact that the parameters that may be effective in COPD self-management have only been researched to a limited extent.…”
Section: F I G U R Ementioning
confidence: 64%
“…In our study, the mean dose at a stable state at 6 months was 2.88 ± 1.745. 28 Zhang et al concluded in their study that the DOSE index stays significant when comparing the change between the outcomes between the periods of the study. They demonstrated the relative predictability of the DOSE index as a measure of health outcomes among a group of Chinese patients.…”
Section: Dose Indexmentioning
confidence: 98%